2007
DOI: 10.1186/1471-2202-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival of adult neurons lacking cholesterol synthesis in vivo

Abstract: Background: Cholesterol, an essential component of all mammalian plasma membranes, is highly enriched in the brain. Both during development and in the adult, brain cholesterol is derived from local cholesterol synthesis and not taken up from the circulation. However, the contribution of neurons and glial cells to total brain cholesterol metabolism is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 29 publications
(34 reference statements)
2
87
0
Order By: Relevance
“…48 Furthermore, it was shown that some adult neurons no longer require endogenous cholesterol synthesis and can fully meet their cholesterol needs by uptake from their surroundings. 49 Therefore, the neuroprotective effects demonstrated by the present work are probably cholesterol independent.…”
Section: Possible Statin Mechanisms Involved In Functional Neuroprotementioning
confidence: 92%
“…48 Furthermore, it was shown that some adult neurons no longer require endogenous cholesterol synthesis and can fully meet their cholesterol needs by uptake from their surroundings. 49 Therefore, the neuroprotective effects demonstrated by the present work are probably cholesterol independent.…”
Section: Possible Statin Mechanisms Involved In Functional Neuroprotementioning
confidence: 92%
“…Subsequent investigations generated conditional mouse lines, with cell-type deletion of squalene synthase and thus cholesterol production in specific cells in the brain. When squalene synthase was eliminated only in myelinating glia cells (41,42), mutant animals were born but showed severe hypomyelination, and one third of the newborn died. When squalene synthase was deleted embryonically in neuronal and glial precursors, no pups were born (41,42), highlighting the importance of brain cholesterol synthesis during development for fetal survival.…”
Section: Fig 6 Expression Of Hsd17b7 In the Embryo By In Situ Hybrimentioning
confidence: 98%
“…When squalene synthase was eliminated only in myelinating glia cells (41,42), mutant animals were born but showed severe hypomyelination, and one third of the newborn died. When squalene synthase was deleted embryonically in neuronal and glial precursors, no pups were born (41,42), highlighting the importance of brain cholesterol synthesis during development for fetal survival. Our deletion of Hsd17b7, the last enzyme in the cholesterol biosynthetic pathway to be discovered, further establishes the importance of cholesterol synthesis in brain development.…”
Section: Fig 6 Expression Of Hsd17b7 In the Embryo By In Situ Hybrimentioning
confidence: 98%
“…Glutamate re-uptake is believed to promote the release of ascorbate via heteroexchange at the site of glutamate transport. Ascorbate release, in turn, may modulate the postsynaptic action of glutamate by blocking NMDA receptors (Kiyatkin and Rebec 1998;Rebec and Sandstrom 2007).…”
Section: Introductionmentioning
confidence: 99%